Hybrid QM/MM study on the deglycosylation step of chitin hydrolysis catalysed by chitinase B from Serratia marcescens - Jitrayut Jitonnom (2018)
Chitinase B (ChiB) from Serratia marcescens is an exo-chitinase that degrades chitin chains from the non-reducing end by cleaving off a dimer or trimer sugar product. This enzyme features the substrate-assisted mechanism for the cleavage of the β-1,4- glycosidic bond. In this study, the deglycosylation step of chitin hydrolysis catalysed by S. marcescens ChiB is investigated by hybrid QM/MM method. Potential energy surface calculated at AM1/CHARMM22 level shows the presence of two transition states (TS1 and TS2) indicating that the deglycosylation path follows a stepwise mechanism in which the nucleophilic attack of catalytic water at the anomeric carbon occurs as the first step followed by proton abstraction. The calculated potential energy barriers for TS1 and TS2 are 26.8 and 4.0 kcal/mol, suggesting that the nucleophilic attack by water molecule is the rate-limiting step for the deglycosylation. In addition, an oxocarbenium-like character in TS1 can also be captured. © 2011 by Maejo University, San Sai, Chiang Mai, 50290 Thailand.